Elucidating the Positive Side of the Work-Family Interface on International Assignments: A Model of Expatriate Work and Family Performance - Lazarova, Mila; Westman, Mina; Shaffer, Margaret A. (Academy of Management Review, 2010)
Drawing on both Job Demands-Resources theory and contagion theory, we conceptualize cognitive, affective, and conative influences on expatriate work role and family role performance. We clarify expatriate adjustment by expanding the concept to capture family role adjustment and by mapping relationships among the forms of adjustment. We also highlight the mediating role of engagement for understanding the influence of adjustment on role performance, and we consider spillover across work and family contexts and crossover between expatriates and partners.